2021
DOI: 10.1038/s41598-021-88488-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of antidiabetic medication and statins with survival from ductal and lobular breast carcinoma in women with type 2 diabetes

Abstract: We investigated the survival of female patients with pre-existing type 2 diabetes (T2D) diagnosed with invasive ductal carcinoma (IDC) and invasive lobular carcinoma (ILC) of breast, in relation to the use of metformin, other antidiabetic medication (ADM) and statins. The study cohort consisted of 3,165 women (2,604 with IDC and 561 with ILC). The cumulative mortality from breast cancer (BC) and from other causes was calculated using the Aalen-Johansen estimator. The cause-specific mortality rates were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…On the other hand, statins have received special attention for their pleiotropic effects, including anti-inflammatory and antitumor potential . A large number of clinical and epidemiological studies have described the anticancer properties of statins, but the evidence for the anticancer effects of statins is inconsistent . In a cohort of 3165 women with breast cancer, statin use was consistently associated with reduced mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, statins have received special attention for their pleiotropic effects, including anti-inflammatory and antitumor potential . A large number of clinical and epidemiological studies have described the anticancer properties of statins, but the evidence for the anticancer effects of statins is inconsistent . In a cohort of 3165 women with breast cancer, statin use was consistently associated with reduced mortality.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 6 A large number of clinical and epidemiological studies have described the anticancer properties of statins, but the evidence for the anticancer effects of statins is inconsistent. 4 , 5 , 6 , 17 In a cohort of 3165 women with breast cancer, 17 statin use was consistently associated with reduced mortality. In a retrospective analysis of 748 patients with non–small cell lung cancer, Atkins et al 18 reported statin use as an independent predictor of all-cause death.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were categorized into mutually exclusive and collectively exhaustive cohorts based on the type of β-blocker they used. Covariates like age, sex, race, ethnicity, BC as the first cancer, stage of BC, subtype of BC, use of statins due to their effects on BC mortality ( Lv et al, 2020 ; Hosio et al, 2021 ; Kim et al, 2022 ; Zhao et al, 2022 ), Charlson comorbidity index, and the year of BC diagnosis were measured. The all-cause mortality and BC mortality were the outcomes for this study, and patients were followed from incident BC diagnosis until the earliest of all-cause mortality, discontinuation of the index β-blocker, switching or concomitant use of comparator β-blockers, or the end of the study period (31 December 2015).…”
Section: Methodsmentioning
confidence: 99%
“…An ongoing trial (NCT01302379) is evaluating the impact of lifestyle control or diet plus metformin or placebo in nondiabetic patients with breast cancer history. The combination of metformin with therapies targeting other metabolic syndrome factors, such as statins, could enhance metformin’s antitumoral properties [ 134 ]. This is the primary objective of the so-called METRICS trial (NCT02201381), designed to evaluate the safety, tolerability, and efficacy of metabolic combination treatments including metformin, atorvastatin, doxycycline, and mebendazole in breast cancer.…”
Section: Metformin In Breast Cancermentioning
confidence: 99%